Sulfur isotope fractionation between aqueous and carbonate-associated sulfate in abiotic calcite and aragonite. (1st July 2020) - Barkan, Yigal; Paris, Guillaume; Webb, Samuel M.; Adkins, Jess F.; Halevy, Itay
Abstract: Sulfate (SO4 2− ) incorporated into calcium carbonate minerals enables measurements of sulfur (S) isotope ratios in carbonate rocks. This Carbonate Associated Sulfate (CAS) in marine carbonate minerals is thought to faithfully represent the S isotope composition of the seawater sulfate incorporated into the mineral, with little or no S isotope fractionation in the process. However, comparison between different calcifying species reveals both positive and negative S isotope fractionation between CAS and seawater sulfate, and a large range of S isotope ratios can be found within a single rock sample, depending on the component measured. To better understand the isotopic effects associated with sulfate incorporation into carbonate minerals, we precipitated inorganic calcite and aragonite over a range covering more than two orders of magnitude of sulfate concentration and precipitation rate. Coupled measurements of CAS concentration, S isotope composition and X-ray absorption near-edge spectra (XANES) permit characterization and explanation of the observed dependence of S isotope fractionation between CAS and aqueous sulfate (CAS-SO4 2− isotope fractionation) on sulfate concentration and precipitation rate. In aragonite, the CAS-SO4 2− isotope fractionation is 1.0 ± 0.3‰ and independent of the sulfate (and CAS) concentration. In contrast, the CAS-SO4 2− isotope fractionation in calcite covaries strongly with the sulfate concentration and weakly with the precipitation rate, between values of 1.3 ± 0.1 and 3.1 ± 0.6‰. We suggest that the correlation between aqueous sulfate concentration and CAS-SO4 2− isotope fractionation in calcite reflects a dependence of the equilibrium S isotope fractionation on the concentration of CAS, through the effect of the sulfate impurity on the carbonate mineral's energetic state.